Public and user participation in public service delivery: tensions in policy and practice - Martin, Graham P. (Wiley, 2009)
Social-scientific analysis of public-participation initiatives has proliferated in recent years. This review article discusses some key aspects of recent work. Firstly, it analyses some of the justifications put forward for public participation, drawing attention to differences and overlaps between rationales premised on democratic representation/representativeness and those based on more technocratic ideas about the knowledge that the public can offer. Secondly, it considers certain tensions in policy discourses on participation, focusing in particular on policy relating to the National Health Service and other British public services. Thirdly, it examines the challenges of putting a coherent vision for public participation into practice, noting the impediments that derive from the often-competing ideas about the remit of participation held by different groups of stakeholders. Finally, it analyses the gap between policy and practice, and the consequences of this for the prospects for the enactment of active citizenship through participation initiatives.